2013
DOI: 10.1021/cb400490k
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Downregulation of PmrAB Reverses Lipid A Modification and Breaks Colistin Resistance

Abstract: Infections caused by multi-drug resistant bacteria, particularly Gram-negative bacteria, are an ever-increasing problem. While the development of new antibiotics remains one option in the fight against bacteria that have become resistant to currently available antibiotics, an attractive alternative is the development of adjuvant therapeutics that restore the efficacy of existing antibiotics. We report a small molecule adjuvant that suppresses colistin resistance in multidrug resistant Acinetobacter baumannii a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 22 publications
1
57
3
Order By: Relevance
“…Examples of compounds that enhance antibiotic activity: (A) FDA-approved serine β -lactamase inhibitor clavulanic acid; 18c (B) MBL inhibitor aspergillomarasmine A (AMA) restores meropenem activity against several Gram-negative species; 19 (C) AME inhibitor exhibits synergism with kanamycin A against E. faecium ; 38 (D) efflux pump inhibitor Phe-Arg- β -naphthylamide (PA β N) increases the susceptibility of P. aeruginosa to levofloxacin; 39 (E) pentamidine perturbs the Gram-negative membrane and sensitizes the bacteria to antibiotics whose activity is ordinarily limited to Gram-positive bacteria; 26a (F) inhibitor of BlaR1 phosphorylation in MRSA increases susceptibility to β -lactam antibiotics; 27 (G) 2-aminoimidazole derivative interferes with TCS signaling in A. baumannii to suppress colistin resistance; 14b (H) quorum sensing inhibitor Hamamelitannin increases the sensitivity of S. aureus biofilms to several classes of antibiotics; 30b (I) previously approved opioid-receptor agonist loperamide potentiates the effects of tetracycline antibiotics against several Gram-negative bacteria. 34b …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Examples of compounds that enhance antibiotic activity: (A) FDA-approved serine β -lactamase inhibitor clavulanic acid; 18c (B) MBL inhibitor aspergillomarasmine A (AMA) restores meropenem activity against several Gram-negative species; 19 (C) AME inhibitor exhibits synergism with kanamycin A against E. faecium ; 38 (D) efflux pump inhibitor Phe-Arg- β -naphthylamide (PA β N) increases the susceptibility of P. aeruginosa to levofloxacin; 39 (E) pentamidine perturbs the Gram-negative membrane and sensitizes the bacteria to antibiotics whose activity is ordinarily limited to Gram-positive bacteria; 26a (F) inhibitor of BlaR1 phosphorylation in MRSA increases susceptibility to β -lactam antibiotics; 27 (G) 2-aminoimidazole derivative interferes with TCS signaling in A. baumannii to suppress colistin resistance; 14b (H) quorum sensing inhibitor Hamamelitannin increases the sensitivity of S. aureus biofilms to several classes of antibiotics; 30b (I) previously approved opioid-receptor agonist loperamide potentiates the effects of tetracycline antibiotics against several Gram-negative bacteria. 34b …”
Section: Figurementioning
confidence: 99%
“…Finally, adjuvants that increase bacterial susceptibility to antibiotics for which toxicity is an issue, such as colistin, 13 would allow these antibiotics to be efficacious at lower doses, thereby mitigating potential side effects. The identification of nonbactericidal adjuvant compounds holds several advantages over the development of new antibiotics, perhaps the most significant being that evolutionary pressure on bacteria to evolve resistance to a compound that does not exert bactericidal or growth inhibitory effects appears to be abated, 14 whereas it is known that optimally designed combination antibiotic therapies have the potential to slow resistance evolution. 15 Another advantage is a result of the fact that truly novel antibiotic targets are rare given both the finite number of essential genes and the extensive exploration that this approach has already received.…”
mentioning
confidence: 99%
“…The already inadequate antibiotic arsenal for A. baumannii due to its inherent and rapidly acquiring antibiotic resistance makes this bacterium a threat to the global public health. A. baumannii have become resistant to carbapenems and more importantly to the last resort antibiotics such as colistin and tigecycline [45,46]. Colloquially, A. baumannii is referred to as 'Iraqibacter' due to its seemingly sudden emergence in military treatment facilities during the Iraq War.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…We recently established that the 2-aminoimidazole (2-AI) compound 1 is capable of reversing colistin resistance in multiple primary clinical isolates of two of the four Gram-negative ESKAPE pathogens: K. pneumoniae , and A. baumannii . 11 Against several strains of both bacteria, the minimum inhibitory concentration (MIC) of colistin was lowered from 512 to ≤4 (in some cases as low as 0.25) µg/mL in the presence of 30 µM (8.4 µg/mL) 1 . Mechanistic studies revealed that treatment of colistin-resistant A. baumannii with 1 led to downregulation of the PmrAB two-component system while mass spectrometry demonstrated reversal of the phosphoethanolamine modification of lipid A responsible for colistin resistance in A. baumannii .…”
Section: Introductionmentioning
confidence: 99%